An experimental study of how hydraulic transients cause mobilisation of material within drinking water distribution systems. (15th April 2021) - Weston, S.L.; Collins, R.P.; Boxall, J.B.
Abstract: This paper provides new insight into how the hydraulic transients that occur within drinking water distribution networks can mobilise material adhered to the pipe wall and hence cause unacceptable water quality and customer dissatisfaction. Results are reported from extensive, representative, physical experiments covering a wide range of repeatable rapidly accelerating and decelerating hydraulic conditions. Novel time synchronous analysis shows that mobilisation always occurs in the first dynamic surge of the transient; however, differences in the physical processes that govern mobilisation were observed between the two groups of transient type studied. A function to estimate the mobilising force is proposed and applied to the physical experiments performed. The research provides important insights for identifying and understanding the mechanisms and forces induced during transients, vital for ensuring the supply of safe drinking water in operational distribution systems. Graphical Abstract: Image, graphical abstract